2012
DOI: 10.1371/journal.pgen.1002863
|View full text |Cite
|
Sign up to set email alerts
|

UNC-40/DCC, SAX-3/Robo, and VAB-1/Eph Polarize F-Actin during Embryonic Morphogenesis by Regulating the WAVE/SCAR Actin Nucleation Complex

Abstract: Many cells in a developing embryo, including neurons and their axons and growth cones, must integrate multiple guidance cues to undergo directed growth and migration. The UNC-6/netrin, SLT-1/slit, and VAB-2/Ephrin guidance cues, and their receptors, UNC-40/DCC, SAX-3/Robo, and VAB-1/Eph, are known to be major regulators of cellular growth and migration. One important area of research is identifying the molecules that interpret this guidance information downstream of the guidance receptors to reorganize the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
(94 reference statements)
5
57
0
Order By: Relevance
“…Many of these proteins are enriched in the nervous or immune systems, although others are widely expressed (Table S2). Of these, only five, including PCDH10, PCDH19, the netrin receptor DCC (Bernadskaya et al, 2012; Stavoe et al, 2012), the Slit receptor ROBO1 (Bernadskaya et al, 2012), and the epithelial Na(+) channel ENaC (Karpushev et al, 2011) have been previously shown to interact with the WRC biochemically or genetically. Furthermore, only a small number have been previously connected with the actin cytoskeleton (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these proteins are enriched in the nervous or immune systems, although others are widely expressed (Table S2). Of these, only five, including PCDH10, PCDH19, the netrin receptor DCC (Bernadskaya et al, 2012; Stavoe et al, 2012), the Slit receptor ROBO1 (Bernadskaya et al, 2012), and the epithelial Na(+) channel ENaC (Karpushev et al, 2011) have been previously shown to interact with the WRC biochemically or genetically. Furthermore, only a small number have been previously connected with the actin cytoskeleton (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to PCDH10 and PCDH19, the WIRS proteins DCC, ROBO and the epithelial sodium channel ENaC (gamma subunit) have been genetically linked to the WRC. DCC and ROBO differentially regulate the abundance and subcellular localization of the WRC to control the actin cytoskeleton in C. elegans embryonic epidermis (Bernadskaya et al, 2012). The WRC and Rac1 were found to be essential in regulating the activity of ENaC (Karpushev et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Important components of these pathways are the GTPases and their regulators, including CED-10 (Rac), CDC-42, MIG-2 (RhoG), UNC-73 (Trio), TIAM-1, and CED-5 (Dock180) (Lundquist et al 2001;Gitai et al 2003;Shakir et al 2008;Demarco and Lundquist 2010;Bernadskaya et al 2012;Demarco et al 2012). In addition to the pathways already noted, a wide variety of other effectors has been implicated in axon guidance, including MIG-15 (NIK) (Poinat et al 2002;Shakir et al 2006;Teulière et al 2011), AGE-1 (PI3K) (Chang et al 2006), MAX-1 (Huang et al 2002), MAX-2 (PAK) (Lucanic et al 2006), UNC-51 (ATG1) (Lai and Garriga 2004), and ANI-1 (anillin) (Tian et al 2015), as well as other phosphatases and kinases.…”
Section: Regulation Of the Actin Cytoskeleton In Axon Outgrowthmentioning
confidence: 99%
“…It is thought that the WAVE/SCAR complex is activated through membrane recruitment by CED‐10/Rac. Moreover, the three receptors that, so far, have been described as involved in cell guidance UNC‐40/DCC, SAX‐3/Robo, and VAB‐1/Eph regulate the abundance and subcellular localization of CED‐10/Rac, the WAVE/SCAR actin nucleation complex and F‐actin in the embryonic epidermis 35.…”
Section: Embryonic Cell Movements and Neuronal Development Are Regulamentioning
confidence: 99%